Investment chart patterns when the market needs a rest - Kahn, Michael N. (FTPress Delivers, 2010)
"This Element is an excerpt from Technical analysis plain and simple: charting the markets in your Language (ISBN: 9780137042012) by Michael N. Kahn. Discover the little-known technical patterns that reveal when the market's headed sideways"--Resource description page.
Resource description page (viewed July 28, 2010)
Keywords: Investment analysis; Corporations -- Finance; Business enterprises -- Finance; Analyse financière; BUSINESS & ECONOMICS; Finance; Corporations; Finance; Business enterprises; Finance; Finance; Business & Economics; Investment & Speculation